PENGARUH INOVASI DESAIN, KUALITAS PRODUK, MEDIA DIGITAL DAN DUKUNGAN PEMERINTAH DALAM MENINGKATKAN DAYA SAING PADA PRODUK TRADISIONAL TAPIS LAMPUNG - Irawan, Heri Agus; Lukman, Iing; Nurbaiti, Nurbaiti (Jurnal Jejama Manajemen Malahayati, 2021)
Purpose this study aims to determine how the influence of design innovation, product quality, digital media and government support in increasing competitiveness. The type of research used in this research is field research (field research). The population in this study were all customers who bought airlangga tapis lampung products in untung suropati bandar lampung in 2020. Sampling using non-probability sampling technique used in this study was incidental sampling. The results of this study indicate that design innovation, digital media and government support have an effect on increasing competitiveness, while liquidity, product quality have no effect on increasing competitiveness. The research is focused on the analysis of design innovations of the lampung airlangga tapis msmes. Research is focused on improving product quality in lampung airlangga tapis smes. This research is focused on introducing lampung tapis products through digital media. This research is focused on increasing government support for tapis lampung airlangga smes.Keywords: Design Innovation, Product Quality, Digital Media, Government Support, And In crease Competitiveness.